2013
DOI: 10.1007/s00415-013-6945-8
|View full text |Cite
|
Sign up to set email alerts
|

Pisa syndrome in Parkinson’s disease: an electrophysiological and imaging study

Abstract: The pathophysiology of postural abnormalities in patients with Parkinson's disease is poorly understood. In the present study, 13 patients with Pisa syndrome (PS) underwent EMG study of paraspinal lumbar (L2-L4) and thoracic (T8-T10) muscles, and of non-paraspinal muscles. Patients also underwent a whole spine X-ray and an MRI assessment of paraspinal muscles (L1-S1). The EMG evaluation disclosed two main patterns: patients with pattern I (n = 6, hyperactivity of lumbar paraspinals ipsilateral to the trunk lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 27 publications
6
83
1
Order By: Relevance
“…72 More recently, a magnetic resonance imaging study showed bilateral paraspinal lumbar muscle atrophy that was unrelated to the side affected by the deviation, and more pronounced in hypoactive muscles as shown by EMG recordings. 73 Although these data are difficult to interpret, they do not support the notion that musculoskeltal mechanisms play a primary role in Pisa syndrome. Moreover, primary myopathy would also be incompatible with the rapid onset of Pisa syndrome seen after medication changes or surgical treatment for PD.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 51%
See 1 more Smart Citation
“…72 More recently, a magnetic resonance imaging study showed bilateral paraspinal lumbar muscle atrophy that was unrelated to the side affected by the deviation, and more pronounced in hypoactive muscles as shown by EMG recordings. 73 Although these data are difficult to interpret, they do not support the notion that musculoskeltal mechanisms play a primary role in Pisa syndrome. Moreover, primary myopathy would also be incompatible with the rapid onset of Pisa syndrome seen after medication changes or surgical treatment for PD.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 51%
“…Electromyographic (EMG) recording of paraspinal muscles failed to show any pattern of denervation or myopathy, 36,72,73 except in 2 of 26 patients in one study. 7 Very few imaging studies have been performed on the paraspinal muscles.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
“…This suggests that the drug alone is probably not sufficient to induce the syndrome, but a combination of genetic and clinical PD characteristics might be needed [4]. On this regard, it has been suggested that PS may represent a complication of advanced PD in patients showing marked asymmetry of symptoms, and detectable hyperactivity of the paravertebral muscles on the less affected side, as we observed in our patient [5].…”
mentioning
confidence: 54%
“…The aim was to 1) investigate activation pattern of the axial paraspinal muscle and 2) find signs of possible denervation or myopathy. Tinazzi et al 50 detected two different patterns of muscular activation: a hyperactivity of lumbar paraspinals ipsilateral to trunk bending side and hyperactivity of paraspinals contralateral to trunk bending side. These observations suggest that a dystonic activity could play a role in determining the bending ipsilaterally to PS and that the contralateral excessive muscle activation represents a compensatory mechanism.…”
Section: Pathophysiologymentioning
confidence: 99%